1993
DOI: 10.1128/jvi.67.10.6136-6151.1993
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structure of the V2 domain of human immunodeficiency virus type 1 surface glycoprotein gp120 with a panel of eight monoclonal antibodies: human immune response to the V1 and V2 domains

Abstract: We have analyzed a panel of eight murine monoclonal antibodies (MAbs) that depend on the V2 domain for binding to human immunodeficiency virus type 1 (HlV-1) gpl20. Each MAb is sensitive to amino acid changes within V2, and some are affected by substitutions elsewhere. With one exception, the MAbs were not reactive with peptides from the V2 region, or only poorly so. Hence their ability to bind recombinant strain IIIB gpl20 depended on the preservation of native structure. Three MAbs cross-reacted with strain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
125
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(137 citation statements)
references
References 55 publications
(81 reference statements)
12
125
0
Order By: Relevance
“…An involvement of the V2 loop in the gp120 intersubunit contact site is also consistent with a number of reports suggesting that epitopes within this domain are less accessible to MAb binding to cell surface-expressed versus soluble purified gp120 (34,37,39). Moreover, it has also been shown that sera from infected individuals have few antibodies against V1/V2 epitopes (25). Within the V2 domain, it appears that epitopes located at the tip of the loop are relatively more occluded in cell surface-expressed gp120 than those in the N-terminal flank (37), supporting the role of the tip segment in association.…”
Section: Discussionsupporting
confidence: 90%
“…An involvement of the V2 loop in the gp120 intersubunit contact site is also consistent with a number of reports suggesting that epitopes within this domain are less accessible to MAb binding to cell surface-expressed versus soluble purified gp120 (34,37,39). Moreover, it has also been shown that sera from infected individuals have few antibodies against V1/V2 epitopes (25). Within the V2 domain, it appears that epitopes located at the tip of the loop are relatively more occluded in cell surface-expressed gp120 than those in the N-terminal flank (37), supporting the role of the tip segment in association.…”
Section: Discussionsupporting
confidence: 90%
“…Neutralizing antisera and mAbs have been raised against gp120 in the form of recombinant or purified glycoprotein or synthetic peptides, or during natural infection with the virus . For many mAbs, their epitopes have been mapped by analysis of their binding to synthetic peptides (5-16, 18, 21, 22, 24), recombinant glycoproteins containing site-directed mutations (25)(26)(27), or a combination of both strategies (19,20,23). Such analyses have allowed a partial understanding of the exposure and spatial relationship of these mAb epitopes on gp120 (19,20,(22)(23)(24)(25)(26)(27)(28).…”
Section: Sllmmarymentioning
confidence: 99%
“…This is important not only when comparing experimental results within the laboratory, but also when comparing results with those of other laboratories. In addition to the V3 loop, other neutralizing sites include epitopes in the C2 [Ho et al, 1988] and V2 [Moore et al, 1993] regions of gp120, as well as in gp41 [Dalgleish et al, 1988], and a conformational epitope that overlaps the CD4 binding region of the envelope glycoprotein. Escape from neutralizing antisera may also occur through mutations in one of these epitopes and influence the binding of different antibodies to numerous sites on the protein.…”
Section: Discussionmentioning
confidence: 99%